Ocena ataku na szpital w Kunduzie w świetle międzynarodowego prawa humanitarnego - Szpak, Agnieszka (Polski Przegląd Stosunków Międzynarodowych, 2018)
Evaluation of the attack on the Kunduz hospital in the light of international humanitarian law The article concentrates on the recent US attack on a hospital led by the international non-governmental organization Médecins Sans Frontières. The hospital was located in Kunduz in Afghanistan and the attack took place on October 2, 2015. The author briefly analyses the legality of the attack in the light of international humanitarian law, especially in the light of the rules of targeting military objectives.